Региональная спецификация социокультурных различий в Украине - Макеев, С.; Патракова, А. (Социология: теория, методы, маркетинг, 2004)
Social and cultural spottiness of Ukraine seems to accompany the uneven economic and inconsistent political development of the country for several centuries. And therefore. a “region” is traditionally used in sociology as an independent variable, explaining differences in preferences and desires of the population. Methods helping to determine social and cultural differences are offered in article. The authors consider people’s estimations of political and social events of the past, present and future to be the most important among all parameters that constitute or reveal a respondent’s culture. In such
estimation, personal orientations and values are expressed if not fully then sufficiently definitely.